Flora polínica da reserva do parque estadual das fontes do Ipiranga (São Paulo, SP, Brasil). Famílias: 141-Boraginaceae e 149-Gesneriaceae - Gasparino, Eduardo Custódio [UNESP] (2014)
Pollen grains of four species of Boraginaceae (Cordia sellowiana Cham., Heliotropium indicum L., Tournefortia breviflora DC., T. villosa Salzm. ex DC.) and of two species of Gesneriaceae [Nematanthus villosus (Hanst.) Wiehler, Sinningia allagophylla (Mart.) Wiehler] occurring in the Reserva do Parque Estadual das Fontes do Ipiranga were examined in the present study. Descriptions, illustrations, and observations of all species studied are presented.